دور الكاثبسينB في بيئة الورم عند مريضات سرطان الثدي - بلال, مرام (Latakia University Journal -Medical Sciences Series, 2017)
اهدف الدراسة: دراسة التعبير عن الكاثبسينB (أحد الأنزيمات الحالة للبروتين) في نسج بشرية من سرطان الثدي، وربط النتائج مع المعلومات المتوفرة عن الورم.المواد والطرق: تمت الدراسة على 23 عينة نسيجية من سرطان الثدي مثبتة بالفورم ألدهيد ومغمورة بشمع البارافين، حيث جُمعت العينات من مشفى الأسد الجامعي ومخبر خاص للتشريح المرضي في محافظة اللاذقية، وباستخدام تقنية التلوين المناعي النسيجي تم التحري عن الكاثبسينB في النسج السرطانية،واستخدم نسيج اللوزة كشاهد إيجابي للتلوين بالأضداد.النتائج: ظهر التعبير السيتوبلاسمي للكاثبسين B في نسيج اللوزة في البالعات المتواجدة في المراكز المنتشة إضافة إلى الخلايا البطانية للأوعية الدموية. لوحظ لدى تلوين عينات سرطان الثدي تلون كل من الخلايا الورمية والخلايا البطانية والخلايا المناعية المتسللة في السدى. وقد ارتبط تعبير الخلايا البطانية عن الكاثبسينB بعلاقة هامة إحصائياً مع درجة الورم (p=0.049).الاستنتاجات: أظهرت الدراسة دور الكاثبسينB في تحفيز تشكل الأوعية الجديدة في الورم، ويبقى تحديد العوامل الالتهابية التي تزيد فعالية الكاثبسينBهاماً في تحديد بعض الجزيئات التي يمكن استخدامها كأهداف جزيئية جديدة لعلاج السرطان. Aim: to assess the expression ofcathepsin B(ctsB; an important protease) in human breast cancer and correlate that with the tumor grade.Materials and Methods:Serial sections were obtained from 23 formalin-fixed paraffin embedded breast cancer tissue specimens which were collected from Alasad University Hospital and a pathological laboratory in Lattakia - Syria. Tissues were stained for cathepsin B using immunohistochemistry. Tonsil tissues were also included as a positive control. Results:Positive cytoplasmic staining of CtsB was observed in both follicular macrophages and endothelial cells in tonsil sections. In breast cancer tissues, tumor cells, endothelial cells and stroma stained positive for CtsB. The presence of CtsB in blood endothelium significantly correlated with the tumor grade (p=0.049).Conclusion: These results supported the important role of cathepsin B in tumor progression, particularly in angiogenesis. Future studies should investigate the regulating mechanisms of cathepsin activities within the tumor environment, and that can be considered as new tagets for cancer treatment.